Research Competences Focused on Trainee Teachers in Early Childhood Education - Rodríguez , Diana Isabel Rodríguez; Loor , Maria Isabel González; Correa , Ximena Patricia Curay; Peñas-Moreno , Martha Cecilia (Journal of Ecohumanism, 2024)
This study deals with the research skills of trainee teachers at the early education level at the National University of Education and their valuable contribution to the teaching- learning process of educational research oriented towards the development of their curricular integration work (ICT). The objective is to diagnose the research skills of students in the fifth and seventh cycles of the Early Education course, with the aim of aligning what is learnt in the classroom in the subject of research with the implementation of the end-of-cycle research work known as the Project for the Integration of Knowledge (PIENSA). The methodology applied is framed in a qualitative study, of an interpretative nature, with the use of an interview with the students under study. The results obtained are analysed by means of a first level codification based on the categories of knowledge, skills, abilities, attitudes and effective performance in the research process. The results show that research competences should be strengthened in a logical sequence in educational research that promotes continuous improvement and is adapted to the projects that are developed permanently in each cycle. Furthermore, the fact that there is a convergence of different criteria on the research competences developed prioritises the search for quality in research and the use of methods that contribute effectively to the fulfilment of the objectives set.